2021
DOI: 10.1177/14648849211033434
|View full text |Cite
|
Sign up to set email alerts
|

Journalistic innovation: How new formats of digital journalism are perceived in the academic literature

Abstract: This article carries out a systematic review of the literature analysing the following new journalistic formats: structured journalism, immersive journalism, 360° video reports, virtual reality and augmented reality applied to journalism, newsgames and docugames. To do so, the scientific production examining these formats is first analysed to determine the academic impact of these studies, while identifying their characteristics and tracking their evolution over time. Second, the leading researchers in this fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 74 publications
0
5
0
2
Order By: Relevance
“…The scoping review also entailed interviews with experts, who were identified from the exploratory systematic review. The process for identifying possible interviewees was successfully and methodologically tested in previous studies (Lopezosa et al 2021). Here, we followed what is known as the 'criterion questions' procedure (Valles, 2002) or condition for selection, one of the considerations of which is who possesses the relevant information and who is likely to be willing to answer.…”
Section: Analysis (Extracted Data)mentioning
confidence: 99%
“…The scoping review also entailed interviews with experts, who were identified from the exploratory systematic review. The process for identifying possible interviewees was successfully and methodologically tested in previous studies (Lopezosa et al 2021). Here, we followed what is known as the 'criterion questions' procedure (Valles, 2002) or condition for selection, one of the considerations of which is who possesses the relevant information and who is likely to be willing to answer.…”
Section: Analysis (Extracted Data)mentioning
confidence: 99%
“…La tabla 1 resume los principales aspectos que conforman la revisión de literatura (Lopezosa et al, 2021) realizada en nuestro análisis. Criterios de inclusión y exclusión: Análisis realizado en artículos que cumplan con las condiciones expresadas en la ecuación de búsqueda planteada en el título, abstract o palabras claves.…”
Section: Metodologíaunclassified
“…Their popularity arrived with their implementation in the digital edition of The New York Times in 2007. The success of some newsgames developed by established media outlets at that time, such as Cutthroat Capitalism (2009) or Gauging Your Distraction (2009), drew the attention of game researchers, who started exploring this phenomenon from an academic perspective (e.g., Bogost et al, 2010;Ferrer-Conill et al, 2020;Grace, 2020;Lin & Wu, 2020;Lopezosa et al, 2021).…”
Section: Political Games In Digital Journalismmentioning
confidence: 99%